Next-Generation Data Management: Hybrid Approaches with Cassandra and Gemfire in Financial Services - Subrahmanyam Mamidi, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article examines the strategic implementation of hybrid data architectures in financial services, combining SQL and NoSQL paradigms to address the industry's evolving data management challenges. Through comprehensive analysis of methodology, implementation approaches, and real-world case studies, we demonstrate how purpose-designed hybrid architectures deliver substantial improvements in system performance, operational efficiency, and business agility. The article documents significant gains across critical metrics including transaction processing capacity, query response times, development velocity, and cost efficiency. Our article reveal that successful implementations depend on thoughtful data tiering strategies, appropriate consistency models, and robust security frameworks tailored to financial service requirements. We identify common implementation challenges and provide evidence-based best practices for architecture selection, migration phasing, and operational sustainability. The documented results from trading platforms, customer profile systems, market data distribution, and retail banking implementations collectively demonstrate that hybrid approaches enable financial institutions to maintain transactional integrity while achieving the scalability and flexibility demanded by modern financial applications. This article provides a structured framework for organizations seeking to leverage complementary database technologies to drive competitive advantage in rapidly evolving financial markets.
Keywords: Hybrid Data Architecture; Financial Services Databases; SQL/NoSQL Integration; Data Tiering Strategies; Performance Optimization